Analisis Kaidah Kebahasaan Teks Berita di Website unja.ac.id - Aspinanda, Gemisya; Kusmana, Ade; Yusra, Hilman (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2025)
This study aims to analyze the language rules in writing news on the unja.ac.id website, especially news about outstanding students. The study uses a qualitative approach with a document/text study method. Data in the form of sentences containing the language rules of news texts are taken from news about outstanding students on the website. The results of the study indicate that the language rules of the news texts are lacking: three texts do not use the conjuncition “that”, and two texts do not have temporal conjuctions. Thus, there are still improvements in the use of language rules. Abstrak Penelitian ini bertujuan menganalisis kaidah kebahasaan dalam penulisan berita di website unja.ac.id, khususnya berita tentang mahasiswa berprestasi. Penelitian menggunakan pendekatan kualitatif dengan metode studi dokumen/teks. Data berupa kalimat yang mengandung kaidah kebahasaan teks berita diambil dari berita mahasiswa berprestasi di website tersebut. Hasil penelitian menunjukkan bahwa kaidah kebahasaan teks berita terdapat kekurangan: tiga teks tidak menggunakan konjungsi